Effectiveness of Mobile App-Based Interventions to Support Diabetes Self-Management: A Systematic Review - Dia Amalindah; Agnestria Winarto; Anggun Hidayatur Rahmi (Jurnal Ners, 2020)
Introduction: Diabetes is a major health problem worldwide due to its rapidly growing prevalence and high disease burden. Nowadays, the evolution of mobile technology provides a large number of health-related mobile applications (apps) mainly focusing on the self-management of diabetes. The aim of this paper is to systematically review the effectiveness of mobile app-based self-management interventions on clinical and/or psychological outcomes in patients with type 1 and type 2 diabetes.Methods: A systematic search of four databases (Scopus, Medline, CINAHL, and Proquest) was conducted using the terms "diabetes" AND "self-management" AND "mobile applications" OR "mobile based" OR “smartphone”. Studies published in English from 2016 to 2020 were considered. Only randomized controlled trials (RCTs) for patients with type 1 and type 2 diabetes that reported any of the study outcomes were included. Using our search strategies, we identified 4339 articles. After removing duplicate studies, a total of 12 articles met the inclusion and exclusion criteria included in the review.Results: The majority measured self-monitoring of blood glucose monitoring frequency, glycated hemoglobin (HbA1c) and/or psychological or cognitive outcomes. The most positive findings were associated with mobile app-based health interventions as a behavioral outcome, with some benefits found for clinical and/or psychological diabetes self-management outcomes for patients with type 1 and type 2 diabetes mellitus.Conclusion: Therefore, more research with larger and longer studies to develop  the ideal mobile-app based self-management tool for diabetes is needed.